Morphology of Endometrial Scrapings in Early Spontaneous Abortions - Ishenbek Satylganov1 , Saltanat Osmonalieva2 , Altynai Zhumabekova3 , Vityala Yethindra4 , Gulnara M (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: Study of morphological changes in the endometrium and fetal membranes during spontaneous abortions in 9-12 weeks of pregnancy to clarify the etiopathogenetic mechanisms. Materials and methods: Study material was endometrial scrapings with components of fetoplacental tissue obtained after spontaneous abortions (176 cases) in 9-12 weeks of pregnancy, received at the Republican Pathological Bureau from several City Maternity Hospitals of Bishkek (Kyrgyz Republic). The histological sections were stained with hematoxylin and eosin (H&E), and a mixture of acid fuchsin and picric acid. The Periodic acid–Schiff (PAS) reaction was performed. Results: Of the 176 cases in 80 cases, by the medical reports, pregnant women had concomitant gynecological infectious pathology in the form of chronic endometritis, chronic salpingoophoritis, chlamydia, colpitis, and adnexitis. Histological examination revealed inflammatory changes in the form of deciduitis (24.5% of cases), endometritis (20.5% of cases), villitis (17.3% of cases) in 70% of cases. Pathological changes in the decidual membrane are determined as foci of leukocyte infiltration in 65% of cases, in 30% - foci of necrosis and in 20% - foci of hemorrhage. In 60% of cases, as their combination. Conclusion: Histological examination of endometrial scrapings and fetal membranes after spontaneous abortions in 9-12 week pregnant women, with a history of infectious inflammatory pathology, revealed the tissue inflammatory changes of varying severity, with the following additional microscopic characteristics: the compact arrangement of endometrial glands, weak vascularization of villus chorion; sclerotic, dystrophic, and necrotic changes with hemorrhages in the endometrium and decidual membrane.